INFORMATION SEEKING BEHAVIOUR OF TRAINEE TEACHERS IN SELECTED TEACHER TRAINING COLLEGES IN MALAYSIA - Shanmugam, Ambikapathi (Malaysian Journal of Library and Information Science, 1999)
Investigates the information seeking behaviour of trainee teachers from two teacher training colleges within the state of Johor, Malaysia. A total of 197 pre-service teachers from the fifth semester have been studied. The data-collecting instrument consisted of a questionnaire. The findings revealed that a majority of the trainees’ information needs are focused around their course work and there is a low awareness of information needs that are not related to teaching. More than half of the trainees moderately expressed positive feelings for seeking information. As for negative feelings, the feelings of ’desperate’ was most prevalent. Trainees largely preferred informal and interpersonal sources. Renowned printed sources such as journals, encyclopaedias, and indexes recorded a low frequency of use. The trainees favoured sources in Malay language to English. Even though the student teachers rated public libraries as excellent, they frequented college library most despite rating it as the third best. Accessibility was considered as the most important external attribute of information. Currency and relevancy of information were given high priority amongst the internal attributes. Accessibility to sources and using the OPAC were cited as major problems when locating information. Investigations showed that computers were largely used for typing rather than for seeking and processing information.